Hypoxia Modulates the Swelling‐Activated Cl Current in Human Glioblastoma Cells: Role in Volume Regulation and Cell Survival. Issue 1 (26th August 2016) - Sforna, Luigi; Cenciarini, Marta; Belia, Silvia; Michelucci, Antonio; Pessia, Mauro; Franciolini, Fabio; Catacuzzeno, Luigi
Abstract : The malignancy of glioblastoma multiforme (GBM), the most common human brain tumor, correlates with the presence of hypoxic areas, but the underlying mechanisms are unclear. GBM cells express abundant Cl channels whose activity supports cell volume and membrane potential changes, ultimately leading to cell proliferation, migration, and escaping death. In non‐tumor tissues Cl channels are modulated by hypoxia, which prompted us to verify whether hypoxia would also modulate Cl channels in GBM cells. Our results show that in GBM cell lines, acute application of a hypoxic solution activates a Cl current displaying the biophysical and pharmacological features of the swelling‐activated Cl current (ICl, swell ). We also found that acute hypoxia increased the cell volume by about 20%, and a 30% hypertonic solution partially inhibited the hypoxia‐activated Cl current, suggesting that cell swelling and the activation of the Cl current are sequential events. Notably, the hypoxia‐induced cell swelling was followed by a regulatory volume decrease (RVD) mediated mainly by ICl, swell . Since, a hypoxia‐induced prolonged cell swelling is usually regarded as a death insult, we hypothesized that the hypoxia‐activated Cl current could limit cell swelling and prevent necrotic death of GBM cells under hypoxic conditions. In accordance, we found that the ICl, swell inhibitor DCPIB hampered the RVD process, and more importantly it sensibly increased the hypoxia‐induced necrotic death in these cells. Taken together, these results suggest that Cl channels are strongly involved in the survival of GBM cells in a hypoxic environment, and may thus represent a new therapeutic target for this malignant tumor. J. Cell. Physiol. 232: 91–100, 2017. © 2016 Wiley Periodicals, Inc.